(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
The relationship between Malaysia and Indonesia had already shown conflict since before the confrontation, or konfrontasi. However, after the proposal for the formation of ​​Malaysia was first announced by Tunku Abdul Rahman, the then-Chief Minister of the Federation of Malaya, the relationship between the two countries experienced a period of significant and prominent conflict. This study discusses the Indonesia-Malaysia confrontation and its impact on Penang Port from 1963 to 1966. This study was conducted using qualitative method, specifically the analysis of documents and manuscripts. The references used are primary sources comprising British records and Malaysian official records, while the secondary sources comprise journals, articles, scholarly books, newspapers, and magazines. The economic relationship between Malaysia and Indonesia was severely damaged during the confrontation. The number of imports and exports involving Indonesia at the Penang Port decreased drastically, but did not stop during the confrontation. Nonetheless, upon comparing the overall growth value of trade at Penang Port during the confrontation, the decrease in the amount of trade that occurred between Indonesia and Penang Port was not very significant. Also, this decrease was not mainly caused by the confrontation, but by the sudden drop in iron ore exports. In conclusion, the slight decrease in the total trade at Penang Port during the confrontation was not solely caused by the confrontation itself and the impact on the whole trade performance at Penang Port in the said period was not that significant. Full text: PDF